2021
DOI: 10.2217/cer-2020-0230
|View full text |Cite
|
Sign up to set email alerts
|

Predicting optimal treatment regimens for patients with HR+/HER2- breast cancer using machine learning based on electronic health records

Abstract: Aim: To predict optimal treatments maximizing overall survival (OS) and time to treatment discontinuation (TTD) for patients with metastatic breast cancer (MBC) using machine learning methods on electronic health records. Patients/methods: Adult females with HR+/HER2- MBC on first- or second-line systemic therapy were eligible. Random survival forest (RSF) models were used to predict optimal regimen classes for individual patients and each line of therapy based on baseline characteristics. Results: RSF models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…An observational study by Cui et al in 2021 investigated CDK4/6i treatment usage in nearly 4000 women diagnosed with HR+/HER2− mBC in the USA between 1 January, 2013 and 31 January, 2019 based on data from the Flatiron Health database. In this study, in the 1L and 2L settings, 42.1% and 40.4% of patients received CDK4/6i-based regimens, respectively [ 32 ]. A retrospective study in Germany of data from the real-world registry PRAEGNANT reported a dramatic increase in CDK4/6i usage over time in the 1L setting for mBC, from 14.1% in 2016 when the first CDK4/6i was approved there in November, to 72.2% in 2022 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study by Cui et al in 2021 investigated CDK4/6i treatment usage in nearly 4000 women diagnosed with HR+/HER2− mBC in the USA between 1 January, 2013 and 31 January, 2019 based on data from the Flatiron Health database. In this study, in the 1L and 2L settings, 42.1% and 40.4% of patients received CDK4/6i-based regimens, respectively [ 32 ]. A retrospective study in Germany of data from the real-world registry PRAEGNANT reported a dramatic increase in CDK4/6i usage over time in the 1L setting for mBC, from 14.1% in 2016 when the first CDK4/6i was approved there in November, to 72.2% in 2022 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Machine-learning approaches leveraging real-world data could be considered for predicting optimal treatment for individual patients based on demographic and clinical characteristics. A study that applied machine learning algorithms to real-world data found that less than 50% of patients in the cohort received optimal treatment with CDK4/6i in 1L and 2L as predicted by the model [ 32 ]. Studies focusing on or reporting subgroup outcomes in specific patient populations (e.g., high Eastern Cooperative Oncology Group performance status) would also be helpful given the heterogeneity within mBC.…”
Section: Discussionmentioning
confidence: 99%
“…• Limited patient population and insufficient high-quality data. [ 21,22] Disease progression modeling and digital twins…”
Section: Ai/ml-enabled Pmx Modelingmentioning
confidence: 99%
“…Members were asked to give a high-level overview of AI/ML activities at their respective companies, including how AI/ML was used for internal decision making or regulatory interactions, how AI/ML can improve upon existing methodologies, and the potential challenges for deploying AI/ML more broadly. The results of this survey were shared with the FDA in October of 2021, and are summarized in Table 1, including a list of key references 5,[16][17][18][19][20][21][22][23][24][25][26][27][28] identified by the working group.…”
mentioning
confidence: 99%